2022
DOI: 10.3389/fpls.2022.889604
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mineral Nutrient Efficiency in Genetically Diverse Spinach Accessions by Biochemical and Functional Marker Strategies

Abstract: Leafy vegetable crops are considered as a natural source of mineral nutrients that could decrease the risk factor of many growth issues in children and adults. Spinach is globally considered as the most desirable leafy crop, due to its taste and nutrient richness along with greater nitrate contents and better nitrogen use efficiency. To evaluate the mineral nutrient efficiency of this crop, thirty genetically diverse spinach accessions were analyzed through nutritional and functional marker strategies. The acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
(51 reference statements)
1
9
0
Order By: Relevance
“…Table 2 depicts the mineral composition (mg/kg) of red soko and green soko. The most abundant mineral in both red soko and green soko was potassium followed by calcium, sodium and magnesium but low concentration of zinc, manganese, lead, copper and selenium were found in the two Celosia species [23,41]. This was in accordance with the report of Ayodele and Olajide [42] for Celosia argentea leaves.…”
Section: % Abts + = Absorbance Of Sample X Gradient X Dilution Factorsupporting
confidence: 89%
“…Table 2 depicts the mineral composition (mg/kg) of red soko and green soko. The most abundant mineral in both red soko and green soko was potassium followed by calcium, sodium and magnesium but low concentration of zinc, manganese, lead, copper and selenium were found in the two Celosia species [23,41]. This was in accordance with the report of Ayodele and Olajide [42] for Celosia argentea leaves.…”
Section: % Abts + = Absorbance Of Sample X Gradient X Dilution Factorsupporting
confidence: 89%
“…Minerals are critical components of bone structure and play a significant role in maintaining overall bone health [36]. The results of our study revealed that bone mineral density increases with increasing serum Ca.…”
Section: Discussionmentioning
confidence: 53%
“…Te nitrates, followed by the oxalates, had the highest decline when fermentation techniques were included in the processing. It is desirable that the two compounds are low in foods due to their negative efects on the bioavailability of micronutrients [38]. It is also desirable that the techniques retain the physical attributes, such as the colour of the products.…”
Section: Independent Variablementioning
confidence: 99%